Transformasi Unsur Fisik Pembentuk Sumbu di dalam Alun-Alun Terhadap Kompleks Pemerintah di Jawa - Malonda, Ayesha Aramita; Kusliansjah, Yohanes Karyadi (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2018)
In the past, Alun-alun is united with the Keraton complex and present in an axis. The physical elements which forms an axis in Alun-alun are the two banyan trees that form the orientation towards the government complex (Keraton). As the development progresses, Alun-alun is revitalized to adjust current cultural conditions and to improve the quality of the Alun-alun's hall as the city's identity. This research aimed to determine the representation of physical elements which formed an axis in Alun-alun towards the government complex. Habraken's theory on the physical order was considered adequate to dissect the physical elements which formed Alun-alun and lead to the conclusion of this research. Matters that needs to be identified to reach the interpretation stage were identifying levels in nominal classes, namely major arteries, roads, building elements, partitioning, furniture, bodies and utensils. The results indicated that the axis of Alun-alun towards the current government complex was indicated by the physical form of locating the furniture in one axis, forming the pathways, the hardening of soil at the main entrance area and the addition of gates inside Alun-alun. The conclusion of this research was that in the past, the axis of Alun-alun towards the government complex was formed by the belief and symbolic meanings of its cultural life. Currently the axis was formed from the physical element of complementary facilities or infrastructure of economic and social activities as a representation of the axis in Alun-alun towards the government complex.